Economics, area studies and human development - Gustav Ranis (Yale University, Economic Growth Center, 2009)
This paper suggests that area studies and economics have a better chance to be married successfully if we shift our attention from the exclusive emphasis on economic growth towards improvements in human development, especially the much broadened version of that concept. Different areas are shown to differ substantially in terms of the choices they make among the various independent dimensions of well-being and the various indicators within each dimension. The particular characteristics of each area play an important role in determining the choices societies make and the extent to which they are constrained by their initial conditions.
Keywords: O1; O2; O5; 330; economics; human development; area studies